Aristocratic women and political society in Victorian Britain. - Reynolds, K. D. (Oxford historical monographs, 1998)
This is a study of gender & power in Victorian Britain. It looks at the contribution made by women to the public culture of the British aristocracy in the 19th century, & challenges the view that power & authority were predominantly male attributes.